Beyond Numbers: The Dance of Determinants in Audit Report Timing for Indonesian Stock Exchange Manufacturers (2018-2020) - Sriyunia Anizar; Netty Nurhayati (Islamic University of Kalimantan MAB Banjarmasin, 2024)
The purpose of this research was to determine the effect of audit tenure and Public Accounting Firm (KAP) reputation on the timeliness of submitting financial reports (report lag) of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The samples for this research were collected from 112 companies over a period of 3 years, so the total number of samples obtained were 336. The testing of hypotheses in this research is done using logistic regression. The research results show that tenure audits influence the report lag, but KAP reputation does not influence the report lag